RECOGNITION OF THE ACTION: INTENTIONALITY, ABSENCE, KNOW-HOW AND DECISION - Jefferson, Jadir (Revista Gênero e Interdisciplinaridade, 2026)
This article examines the structure of recognition through a dialogue between analytic philosophy and phenomenology, advancing the thesis that recognition is not merely the identification of an object but the exercise of a dynamic intentional competence structured by horizons of absence. Drawing on John Perry’s (2001) account of the architecture of recognition, the paper argues that the coordination of different modes of presentation requires an experiential dimension that exceeds mere reference. This dimension is clarified through a phenomenological analysis inspired by Edmund Husserl (1982), according to which perceptual presence always entails a field of operative absences that guide anticipation, familiarity, and practical stability. On this basis, the article contends that recognition already involves forms of know-how, thereby dissolving the traditional dichotomy between theoretical cognition and practical competence (Ryle, 1949). Decision-making, in turn, is not an external reflective rupture but the motivational stabilization of a field previously structured by embodied familiarity (Karlsson, 1988). The paper concludes that action motivation emerges from a dynamic intentional organization in which identity, presence, and skill constitute moments of a unified process. Recognition is thus reconceptualized as a foundational structure of action.